2016
DOI: 10.21037/qims.2016.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve head perfusion in normal eyes and eyes with glaucoma using optical coherence tomography-based microangiography

Abstract: Background: To investigate the differences of perfusion in the optic nerve head (ONH) between normal and glaucomatous eyes using optical microangiography (OMAG) based optical coherence tomography (OCT) angiography technique.Methods: One eye from each subject was scanned with a 68 kHz Cirrus 5000 HD-OCT-based OMAG prototype system centered at the ONH (Carl Zeiss Meditec Inc, Dublin, CA, USA). Microvascular images were generated from the OMAG dataset by detecting the differences in OCT signal between consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 24 publications
2
44
0
1
Order By: Relevance
“…The angiogenic vessels visualized here also appeared brighter than their surrounding counterparts (Figure 4). Studies have shown that the OMAG signal is proportional to the flux of red blood cells passing through the vessels (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…The angiogenic vessels visualized here also appeared brighter than their surrounding counterparts (Figure 4). Studies have shown that the OMAG signal is proportional to the flux of red blood cells passing through the vessels (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…12 Consequently, OMAG is being established as a valuable tool for the investigation of ocular diseases both qualitatively 13 and quantitatively. 14 To objectively assess the OCT angiograms, a number of studies have introduced vessel area density (VAD), 15,16 vessel skeleton density (VSD), 15,17 and nonperfusion area. 16 These parameters have been reported useful in the analyses of disease progression in DR and AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a threedimensional (3D) imaging technique that can provide noninvasive, high-resolution cross-sectional images in real time (4,5). As a high-resolution functional extension to OCT, OCT-angiography (OCTA) (6)(7)(8) offers rapid, safe, non-invasive and cost-effective solution to imaging depthresolved microcirculation down to capillary level, which has recently found its way to clinical translation, for example in ophthalmology (9)(10)(11). Optical micro-angiography (OMAG) is introduced based on the observations of complex signal fluctuations, which are hypothesized to be related to moving erythrocytes within functional blood vessels (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%